Czech Republic : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency; Banking Supervision; Insurance Regulation; Securities Regulation; Corporate Governance; and Payment Systems. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The resilience of the Czech financial system to macroeconomic shocks and structural weaknesses has strengthened considerably as a result of recent reform efforts. Stress tests indicate that the Czech banking system now shows only moderate vulnerability to market and credit risks. To enable more effective monitoring of the activities of integrated firms and markets, coordination and cooperation between supervisory agencies requires strengthening. Regarding the nonbanking sectors, the adoption of the mutual fund model for pension funds would improve transparency, and needs to be implemented as soon as possible.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet